Hubungan Profil Hematologi, Protein Urin, Dan Obesitas Ibu Hamil Pada Kejadian Preeklampsia - Rihlatun Namira Sudirman, Siti; Haruna, Nadyah; Nurdin, Azizah; Irnawati, Risma; Gassing, Abdul Qadir (STIKES Ngesti Waluyo, 2024)
Excessive weight gain, abnormal haematological profiles, and the presence of urinary protein in pregnant women with preeclampsia may lead to higher maternal mortality. This study aims to determine the relationship between haematological profiles, urine protein, and obesity in the incidence of preeclampsia. Quantitative analytical approach case-control using secondary data from patient medical records at RSIA Sitti Khadijah 1 Muhammadiyah Makassar from January 2020-August 2022. The research sample included 330 samples consisting of 165 cases and 165 controls. The haematological profiles of pregnant women with preeclampsia showed that the predominant haemoglobin level was normal (p-value = 0.579), normal erythrocytes (p-value = 0.447), abnormal leukocytes (p-value = 0.077), abnormal hematocrit (p-value = 0.218), normal platelets (p-value = 0.692), MCV (p-value 0.729), abnormal MCH (p-value = 0.654), and abnormal MCHC (p-value 0.404). Regarding urine protein, dominantly has positive protein (p-value=0.000). Pregnant women who suffer from preeclampsia were predominantly obese (p-value=0,005). There was no significant relationship between haematological profiles and the incidence of preeclampsia. There is a significant relationship between urine protein and obesity and preeclampsia incidence.